2011
DOI: 10.1007/s10916-011-9729-7
|View full text |Cite
|
Sign up to set email alerts
|

A Data-Mining Framework for Transnational Healthcare System

Abstract: Medical resources are important and necessary in health care. Recently, the development of methods for improving the efficiency of medical resource utilization is an emerging problem. Despite evidence supporting the use of order sets in hospitals, only a small number of health information systems have successfully equipped physicians with analysis of complex order sequences from clinical pathway and clinical guideline. This paper presents a data-mining framework for transnational healthcare system to find alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…They mention that data mining models and results might be shared between different hospitals over a cloud-based server. Nevertheless the authors equal cloud computing with the Internet in general [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They mention that data mining models and results might be shared between different hospitals over a cloud-based server. Nevertheless the authors equal cloud computing with the Internet in general [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…a physical network of many computers [ 5 , 26 , 77 , 84 ]. In five papers the cloud is even equated with the Internet in general [ 8 , 9 , 68 , 71 , 102 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A sizable amount ($37.6 billion) of healthcare costs is attributable to medical errors, 45% of which stems from preventable errors [ 95 ]. To aid in physician decision-making and reduce medical errors, researchers [ 95 ] proposed a data mining-based framework-Sequential Clustering Algorithm.…”
Section: Application Of Analytics In Healthcarementioning
confidence: 99%
“…It is important to note that only 12 papers [3,22,52,60,73,93,96,119,120,124,143,170] state that their research/product was implemented/informed policythis is only 6.9% of the papers surveyed. Previous reviews have found similar results in regards to implementation (e.g.…”
Section: Obtaining the Pathwaymentioning
confidence: 99%